Effects of Five–Year Inorganic and Organic Fertilization on Soil Phosphorus Availability and Phosphorus Resupply for Plant P Uptake during Maize Growth - Jingjing Zhang; Jiong Wen; Tuo Zhang; Yang Zhang; Zhi Peng; Chunchun Tang; Yanan Wang; Shiming Su; Nan Zhang; Xibai Zeng (Agriculture, 2023)
A better understanding of the P dynamic resupply roles of fertilization from soil solids to solution is urgently required to optimize sustainable P fertilizer management practices for efficient supply. A five–year fertilization experiment was used to investigate the effects on soil P fractions and availability, the kinetic P resupply based on a novel simulation technique (Diffusive gradients in thin films (DGT) and DGT–induced fluxes in sediments and soils (DIFS) ) and to identify dominant factors during the maize season under five treatments (no fertilizer (CK), chemical fertilizer (NPK), chemical fertilizer combined with bone meal fertilizer (NPKC), crop straw (NPKS) and bioorganic fertilizer (NPKM)). The results showed that the NPKC and NPKM treatments had higher enhancement effects on Olsen–P and organic P and inorganic Ca2–P, Ca8–P, Al–P and Fe–P at maize growth stages, and they buffered pH decrease to delay the substantial Fe–P and Al–P release until a late stage. Inorganic Ca2–P, Ca8–P, Al–P and Fe–P heavily effected the Olsen–P levels. The NPKS, NPKC and NPKM treatments yielded higher CDGT–P levels and a stronger resupply capacity, reflected by higher R and CE/Csoln and smaller Tc values. The simulation and path model results revealed that the maize plant P uptake was determined by soil P resupply and an inorganic P supply pool. They were positively dominated by soil organic matter (SOM). Our results suggested that organic fertilization, especially NPKC and NPKM treatments, provided greater enhancement effects on the P supply pool and P resupply for higher plant P uptake, identifying them as highly effective P management practices for developing sustainable agriculture.